Effective solubility parameters of sucrose monoester surfactants obtained by inverse gas chromatography - de Schaefer, C. R. (2008)
Two products with a high content of sucrose monoesters were obtained from the commercial products P1670 and S1670, using liquid chromatography. The separation progress was monitored by thin layer chromatography (TLC). Differential scanning calorimetry (DSC) between 293.15 K and 473.15 K was used to define the transition phase temperature of the sucrose ester mixtures. Specific retention volumes of twelve probe solutes were measured at four different temperatures using sucrose monoester blends as stationary phases. These blends were characterized using DSC and inverse gas chromatography (IGC) techniques. The thermodynamic properties determined by IGC show an increase in the solubility in the surfactant mixture as the source fatty acid chain length increases, and a decrease in the solubility with an increase of the monoesters/diesters ratio. The values obtained from "effective solubility parameters" are explained by the presence of mesophases in the products analysed as stationary phases. The values of the effective solubility parameters are lower than those obtained for commercial surfactants.